2008
DOI: 10.1080/01635580802290231
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Copper Excess, Zinc Deficiency, and TP53 Mutations in Esophageal Squamous Cell Carcinoma From Kashmir Valley, India—A High Risk Area

Abstract: Trace element deficiency or excess is implicated in the development or progression in some cancers. Here we report the elevated level of copper and low level of zinc in the plasma of esophageal cancer patients in Kashmir India--a high incidence area. The average level of copper was significantly higher (P < 0.0001) for patients than for controls, with a mean concentration of 169 microg/dl and 149 microg/dl for patients and controls, respectively. The control group consisted of 55 healthy individuals matched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Also, the worse the histological grade in oesophagus squamous cancer, the higher is the copper level. Our finding is in agreement with most of the earlier studies suggesting that in the oesophageal cancer groups serum copper is higher [9][10][11]. Also, copper chelation by chelating agents has antiproliferative effects in many studies [12].…”
Section: Discussionsupporting
confidence: 83%
“…Also, the worse the histological grade in oesophagus squamous cancer, the higher is the copper level. Our finding is in agreement with most of the earlier studies suggesting that in the oesophageal cancer groups serum copper is higher [9][10][11]. Also, copper chelation by chelating agents has antiproliferative effects in many studies [12].…”
Section: Discussionsupporting
confidence: 83%
“…Animal studies have shown that the administration of Zn may slow the progression of induced tumours and studies in humans also show that administration of Zn and other micronutrients may have therapeutic effects in patients with oral precancerous lesions [29]. Low serum Zn concentrations detected in some cancer such as esophageal carcinoma, ovarian cancer, cervical cancer [30,31]. By contrast, high serum level of Zn was detected in liver cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the p53 gene are known to be the most common genetic changes in solid tumors, including esophageal carcinoma [4]. Indeed, the p53 protein regulates the expression of hundreds of genes.…”
Section: Introductionmentioning
confidence: 99%